Type I error rates of the two-sample pseudo-median procedure - Ahad, Nor Aishah; Othman, Abdul Rahman; Syed Yahaya, Sharipah Soaad (Wayne State University, College of Education, 2011)
The performance of the pseudo-median based procedure is examined in terms of controlling Type I error for a two independent groups test.The procedure is a modification of the one-sample Wilcoxon statistic using the pseudo-median of differences between group values as the central measure of location.The proposed procedure was shown to have good control of Type I error rates under the study conditions regardless of distribution type.